2020
DOI: 10.1093/ejo/cjaa038
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction after orthognathic surgery: a 3 year follow-up of 60 high-angle Class II individuals

Abstract: Summary Background and objectives High-angle Class II malocclusion is considered challenging to treat to a stable result and, although studies report treatment outcome in terms of morphology, patient satisfaction has not been addressed. The objectives of the present study were to examine patients’ motives for treatment and satisfaction with the results. Material and methods A structured quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…Yet the mean score is lower at the end of treatment than at one year after surgery, though statistical significance is not reached. The only improvements maintained at the end of the treatment are found in general orthognathic quality of life, oral function and facial aesthetics, supporting recent findings by Torgersbråten et al [28] who reported improvements in oral function, dental and facial appearance three years post-surgery. The results also support the results by Paunonen et al [16], who found improvements in OQLQ in patients treated 4-8 years previously, as we did find changes both in functional and aesthetic issues.…”
Section: Discussionsupporting
confidence: 84%
“…Yet the mean score is lower at the end of treatment than at one year after surgery, though statistical significance is not reached. The only improvements maintained at the end of the treatment are found in general orthognathic quality of life, oral function and facial aesthetics, supporting recent findings by Torgersbråten et al [28] who reported improvements in oral function, dental and facial appearance three years post-surgery. The results also support the results by Paunonen et al [16], who found improvements in OQLQ in patients treated 4-8 years previously, as we did find changes both in functional and aesthetic issues.…”
Section: Discussionsupporting
confidence: 84%
“…The most common reason for seeking orthognathic surgery is the correction of occlusion or oral function [ 24 , 25 , 26 ], followed by facial and psychosocial improvement [ 27 ]. With new procedures, it is therefore essential to evaluate the postoperative occlusion, which is the orthodontic basis for achieving a good final intercuspation and the associated masticatory function.…”
Section: Discussionmentioning
confidence: 99%
“… Overview of rotation errors (yaw, roll, and pitch) concerning studies on virtual planning in orthognathic surgery. Measurements of the present study compared to the results of three systematic reviews (Sys Rev) covering the years 2007–2020 [ 4 , 26 , 35 ]. …”
Section: Figurementioning
confidence: 99%
“…Based on our own experience and available sources, we can conclude that there is a risk that patients may find it difficult to accept their new face after surgery and will need a lot of time to get used to it. It may happen that they will not be satisfied with their new appearance and will have difficulties adapting for the rest of their lives [26]. From the perspective of this problem, it seems important to develop and widely implement 3D modeling as one of the elements of patient preparation for surgery.…”
Section: Discussionmentioning
confidence: 99%